Menumbuhkan Kepedulian Siswa terhadap Lingkungan melalui Program Go-Green di SDN Pajaran I (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
The first step in maintaining and caring for the school environment is to foster student awareness of the importance of preserving the school environment. For this reason, it is necessary to develop a go-green program that aims to foster student awareness of the environment at SDN Pajaran I. Community service is carried out with a community development and participatory approach. The target partner for the community service program is SDN Pajaran I, which technically involves teachers and students of SDN Pajaran I. In realizing student awareness of the environment, a go-green program is needed, in the process education is needed both from counseling and direct practice. The results obtained, students can learn the concept of go-green and its application in the school environment consisting of organic and inorganic waste processing, and procedures for planting bananas, papaya, and kale along with their benefits. It can be concluded that a clean, beautiful, and green environment can create good air potential for health. And the teaching and learning process will take place well and comfortably.